Jejak Nelayan Suku Bugis dalam Implementasi Blue Accounting - Hidayat, Irwan; Jumaidi, Lalu Takdir (Universitas Hamzanwadi, 2025)
Fisheries is an important sector in Indonesia's economy, especially for Bugis villagers who depend on marine resources, amid challenges such as overfishing and damage to marine ecosystems that require more sustainable management. This study aims to explore the experiences of Bugis fishermen in Kampung Bugis Ampenan, West Nusa Tenggara, in applying “Blue Accounting”, which integrates economic, social and environmental values. The method used is a qualitative method of spirituality approach. Data collection techniques with observation, interviews and documentation. The results showed that Bugis fishermen indirectly use Blue Accounting practices, in which recording and reporting fishing activities in detail. Despite being aware of the importance of maintaining the marine ecosystem, Blue Accounting practices are often perceived as an additional burden by Bugis fishermen. This research emphasizes that the successful implementation of Blue Accounting requires support from stakeholders, including government and non-government, to provide the necessary training and resources. The research also shows the importance of integrating local and spiritual values in marine resource management. The research is expected to provide practical recommendations for policy makers in formulating inclusive and sustainable marine resource management strategies.